Informal Apprenticeship Learning Model to Improve Layer Chicken Farm Workers' Competency: A Case Study at CV. Arto Moro Farm - Lasi Purwito (Postgraduate, University of Mataram, 2025)
This research aims to develop a grounded theory model of informal apprenticeship to improve worker competencies at the layer chicken farm CV. Arto Moro Farm, Blitar Regency, East Java. A qualitative approach using grounded theory methodology was employed, with data collection through participatory observation, in-depth interviews, and documentation involving farm owners and workers. Data analysis was conducted through coding stages following grounded theory procedures. The research results show that the apprenticeship process is led by the owner as instructor and takes place in an informal atmosphere with a direct learning model (learning-by-doing). This process successfully transfers knowledge, skills, and attitudes, significantly improving worker competencies. This study contributes an applicable informal apprenticeship model for human resource development in the layer chicken farming sector